2018
DOI: 10.1080/10717544.2018.1494222
|View full text |Cite
|
Sign up to set email alerts
|

Sodium stibogluconate loaded nano-deformable liposomes for topical treatment of leishmaniasis: macrophage as a target cell

Abstract: Topical drug delivery against cutaneous leishmaniasis (CL) signifies an effective alternate for improving the availability and reducing the toxicity associated with the parenteral administration of conventional sodium stibogluconate (SSG) injection. The basic aim of the study was to develop nano-deformable liposomes (NDLs) for the dermal delivery of SSG against CL. NDLs were formulated by a modified thin film hydration method and optimized via Box–Behnken statistical design. The physicochemical properties of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(43 citation statements)
references
References 46 publications
2
41
0
Order By: Relevance
“…The same behavior was observed for the MA solution, although a lower amount of Sb V was detected. Similar results were obtained by Dar et al (2018), who tested nano-deformable liposomes with sodium stibogluconate and the same liposomes in a Carbopol gel on rat skin, and observed a low percentage of Sb V permeated into the receptor compartment and a high percentage was retained in the skin [21]. Other studies with liposomes encapsulating MA, MA combined with oleic acid and MA plus stearylamine also showed low permeation of Sb V across the skin barrier and high retention in mouse skin [22,23].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The same behavior was observed for the MA solution, although a lower amount of Sb V was detected. Similar results were obtained by Dar et al (2018), who tested nano-deformable liposomes with sodium stibogluconate and the same liposomes in a Carbopol gel on rat skin, and observed a low percentage of Sb V permeated into the receptor compartment and a high percentage was retained in the skin [21]. Other studies with liposomes encapsulating MA, MA combined with oleic acid and MA plus stearylamine also showed low permeation of Sb V across the skin barrier and high retention in mouse skin [22,23].…”
Section: Discussionsupporting
confidence: 84%
“…The rheological properties of topical semi-solid dosage forms are important because they influence skin spreadability, adhesion and retention in the application site [21]. The rheological analysis indicated that the MA gel is a pseudoplastic fluid, like most gels reported in the literature, which is ideal for topical administration [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It identifies the relationship between variables and response to obtain the most appropriate conditions for preparation [23]. In the present study, a Box-Behnken Design (BBD), a common response surface methodology, was used to optimize the formulation of RSV-Lips [24,25]. The weight ratio of phospholipid to cholesterol, the weight ratio of phospholipid to drug, and the ultrasonic power value were used as independent variables, while the entrapment efficiency and drug loading capacity were used as response values.…”
Section: Preparation and Optimization Of Rsv-lipsmentioning
confidence: 99%
“…Stibogluconate (sodium antimony gluconate, sodium stibugluconate, pentostam, stibium Sb gluconate) is an anti-parasitic drug that incorporates gluconate into the drug substance. It belongs to the anti-leishmaniasis group of drugs called pentavalent-(V)-antimony compounds in which antimony (Sb) is used (1719). It has been suggested that stibogluconate acts through immune system stimulation, mainly by increasing the amount of peripheral IFN-γ + T cells (20).…”
Section: Stibogluconate In Cancer Immunotherapymentioning
confidence: 99%